2022
DOI: 10.15406/paij.2022.06.00267
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear energy and sustainable development

Abstract: The dependency on combustion of coal, oil and gas for energy cannot be indefinite. Thus, the process of replacing fossil fuels with many energy technologies cannot be avoided in order to combat this high dependency. Nevertheless, we argue that in the long term, nuclear fission technology is the answer to the ever increasing demand for energy. This entails that nuclear fission has to play a major role in suppling energy in this age and beyond. In achieving this, the major aspect is in switching electrical ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…Nuclear energy may supply electricity up to 25% on a world scale by the year 2040. 17 This is because research has shown that nuclear energy is second to hydroelectricity in producing power with low carbon emissions resulting in a safer environment. Worldwide, over fifty countries are utilizing nuclear energy as their source of electricity.…”
Section: Status Of Nuclear Powermentioning
confidence: 99%
“…Nuclear energy may supply electricity up to 25% on a world scale by the year 2040. 17 This is because research has shown that nuclear energy is second to hydroelectricity in producing power with low carbon emissions resulting in a safer environment. Worldwide, over fifty countries are utilizing nuclear energy as their source of electricity.…”
Section: Status Of Nuclear Powermentioning
confidence: 99%
“…When energy exceeding the quark mass energy is added to this system of quarks and gluons, the quarks tend to 'repel' each other resulting in the gluons stretching further. 3 This change in energy can be mathematically be described as…”
Section: Introductionmentioning
confidence: 99%
“…1 This Has resulted in the reduction of the area covered by snow on the globe. 2 Many global forces and events have been correlated to the rise in temperatures. Such events include volcano eruptions as well as radiation variation in many places on the planet.…”
Section: Introductionmentioning
confidence: 99%